MODEL PEMBELAJARAN BERBICARA YANG INTERAKTIF DAN MENYENANGKAN: STUDI KASUS DI UNIVERSITAS MURIA KUDUS - Darmuki, Agus; Alfin Hidayati, Nur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the interactive and enjoyable speaking learning model for PBSI UMK students. The problem faced by PBSI UMK students is the lack of opportunities to speak interactively and enjoyably, which affects their speaking ability. The solution offered is to use an interactive and enjoyable speaking learning model. The purpose of this study was to determine an effective and enjoyable speaking learning model for PBSI UMK students. This study used a case study method with a qualitative approach. The instruments used were observation, interviews, and questionnaires. The subjects of this study were 30 PBSI UMK students who were taking speaking skills courses. The results showed that the interactive and enjoyable speaking learning model for PBSI UMK students was a learning model that used technology, such as online speaking applications, and fun activities, such as role-play and group discussions. Students felt that this learning model helped them improve their speaking skills and made them more confident. The conclusion of this study is that the interactive and enjoyable speaking learning model can improve the speaking skills of PBSI UMK students and make them more confident. Therefore, this learning model can be used as an alternative in improving students' speaking skills.